Risk factors for postoperative cervical haematoma in patients undergoing thyroidectomy: a retrospective, multicenter, international analysis (REDHOT study) - Canu, Gian Luigi; Medas, Fabio; Cappellacci, Federico; Rossi, Leonardo; Gjeloshi, Benard; Sessa, Luca; Pennestrì, Francesco; Djafarrian, Reza; Mavromati, Maria; Kotsovolis, George; Pliakos, Ioannis; Di Filippo, Giacomo; et al. (Frontiers in Surgery, 2023)
Background Postoperative cervical haematoma represents an infrequent but potentially life-threatening complication of thyroidectomy. Since this complication is uncommon, the assessment of risk factors associated with its development is challenging. The main aim of this study was to identify the risk factors for its occurrence. Methods Patients undergoing thyroidectomy in seven high-volume thyroid surgery centers in Europe, between January 2020 and December 2022, were retrospectively analysed. Based on the onset of cervical haematoma, two groups were identified: Cervical Haematoma (CH) Group and No Cervical Haematoma (NoCH) Group. Univariate analysis was performed to compare these two groups. Moreover, employing multivariate analysis, all potential independent risk factors for the development of this complication were assessed. Results Eight thousand eight hundred and thirty-nine patients were enrolled: 8,561 were included in NoCH Group and 278 in CH Group. Surgical revision of haemostasis was performed in 70 (25.18%) patients. The overall incidence of postoperative cervical haematoma was 3.15% (0.79% for cervical haematomas requiring surgical revision of haemostasis, and 2.35% for those managed conservatively). The timing of onset of cervical haematomas requiring surgical revision of haemostasis was within six hours after the end of the operation in 52 (74.28%) patients. Readmission was necessary in 3 (1.08%) cases. At multivariate analysis, male sex (P < 0.001), older age (P < 0.001), higher BMI (P = 0.021), unilateral lateral neck dissection (P < 0.001), drain placement (P = 0.007), and shorter operative times (P < 0.001) were found to be independent risk factors for cervical haematoma. Conclusions Based on our findings, we believe that patients with the identified risk factors should be closely monitored in the postoperative period, particularly during the first six hours after the operation, and excluded from outpatient surgery.